Expression of Armenian case meanings in the Anbarāni dialect of the Talyshi language - Avchyan, Hakob (Bulletin of Yerevan University B: Philology, 2022)
Talysh, a northwestern Iranian language, is traditionally divided into three main dialectical clusters: northern, central and southern. The division of Talysh into three clusters is based on lexical, phonological and grammatical factors. Northern Talysh distinguishes itself from Central and Southern Talysh not only geographically but culturally and linguistically as well. Speakers of Northern Talysh are found almost exclusively in the Republic of Azerbaijan but can also be found in the neighboring regions of Iran. Anbarāni, one of the northern Talysh dialects, is spoken in Ardabil province of the Islamic Republic of Iran, in Anbarān city and the adjacent villages. Talysh has a two-case system, while the Easter Armenian language has seven cases, thus to express the meanings of Armenian cases, a number of adpositions, such as čə, ba, da, anda, ku, o, sa, ro, piu, the connecting vowel -a and several function words, including gorao, baranda, tarafo are used.
Keywords: Talyshi; Northern Talyshi; Anbarāni dialect; Armenian language; Case; Prepositions; Postpositions